2003
DOI: 10.1097/01.ccm.0000053555.78624.0f
|View full text |Cite
|
Sign up to set email alerts
|

Ibutilide versus amiodarone in atrial fibrillation: A double-blinded, randomized study

Abstract: Ibutilide has no significant advantage over amiodarone for the conversion of atrial fibrillation to sinus rhythm in either time to conversion or conversion overall, but severe hypotension was not seen with ibutilide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
24
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 24 publications
7
24
1
Order By: Relevance
“…In a study that randomized patients in a double-blind fashion to either ibutilide or amiodarone, these drugs had comparable conversion rates at 4 hours. 20 Ibutilide was superior in terms of hemodynamic and systemic side effects; hypotension was seen more often in patients receiving amiodarone. 20 Another study, in which 42 stable patients with new atrial fibrillation after cardiac surgery were randomized to oral propafenone (600 mg, single dose), ibutilide (1 mg up to 2 doses if necessary), or rate control with, preferably, a ␤-blocker, ibutilide was significantly superior to propafenone in terminating the arrhythmia.…”
Section: Use Of Ibutilide In Postoperative Atrial Fibrillation and Flmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study that randomized patients in a double-blind fashion to either ibutilide or amiodarone, these drugs had comparable conversion rates at 4 hours. 20 Ibutilide was superior in terms of hemodynamic and systemic side effects; hypotension was seen more often in patients receiving amiodarone. 20 Another study, in which 42 stable patients with new atrial fibrillation after cardiac surgery were randomized to oral propafenone (600 mg, single dose), ibutilide (1 mg up to 2 doses if necessary), or rate control with, preferably, a ␤-blocker, ibutilide was significantly superior to propafenone in terminating the arrhythmia.…”
Section: Use Of Ibutilide In Postoperative Atrial Fibrillation and Flmentioning
confidence: 99%
“…19 The conversion rates were higher in all doses for atrial flutter compared with atrial fibrillation. Ibutilide's efficacy and safety profile was compared with those of amiodarone and propafenone in terminating postoperative atrial fibrillation 20,21 (Table 1). It was as effective as amiodarone in converting postoperative atrial fibrillation; however, the time to cardioversion was significantly lower in patients receiving ibutilide.…”
Section: Use Of Ibutilide In Postoperative Atrial Fibrillation and Flmentioning
confidence: 99%
“…Previous studies have reported that ibutilide may precipitate ventricular arrhythmias in 3.6% to 8.3% of patients [13][14][15]. Non-arrhythmogenic adverse effects were rare and typically similar in frequency to those experienced with placebo [13][14][15][16]. It is worth noting, that ibutilide exerted no negative hemodynamic effects even in patients with markedly reduced left ventricular function [17].…”
Section: Introductionmentioning
confidence: 79%
“…Together, the two clinical trials demonstrated that ibutilide administration is superior to placebo in terminating atrial fibrillation/flutter. Other clinical results from two randomized, double blind, prospective trials showed that ibutilide is also effective in terminating atrial fibrillation in 44-45% and atrial flutter in 78% of stable patients after cardiac surgery, respectively [15,16]. Previous studies have reported that ibutilide may precipitate ventricular arrhythmias in 3.6% to 8.3% of patients [13][14][15].…”
Section: Introductionmentioning
confidence: 91%
“…Ibutilide is a class III antiarrhythmic agent that can convert AF to sinus rhythm more rapidly than can procainamide or sotalol. It has been shown that ibutilide has no significant advantage compared with amiodarone for the conversion of AF but severe hypotension was not seen with ibutilide 23 . For acute AF, conversion to sinus rhythm with ibutilide is about 59%, but there is 1.7% risk of polymorphic ventricular tachycardia with this drug.…”
Section: Pharmacological Cardioversionmentioning
confidence: 99%